Environmental Regulation of Photosynthetically Produced Dissolved Organic Carbon by Phytoplankton Along a Subtropical Estuarine Bay - Kang, Jianhua; Luo, Zhaohe; Mohamed, Hala. F.; Lin, Yili; Huang, Shuhong; Wang, Yu; Lan, Wenlu (Frontiers in Marine Science, 2022)
Photosynthetically produced dissolved organic carbon(PDOC) released by marine phytoplankton, which is often neglected in the estimation of global marine primary productivity and carbon sequestration capacity,has an important significance on marine carbon cycle as well as carbon balance model-building.This paper studied the issue of PDOC and its environmental regulation mechanism by carrying out field investigation and lab experiments in an estuarine bay during southwest and northeast monsoon.We used the percentage of extracellular release(PER) as a key indicator to evaluate the contribution of PDOC to total primary productivity(TPP),compared PER between different seasons and sectors,then analyzed the inter-relationship between PDOC and bacterial carbon demand(BCD),size-fractionated phytoplankton,BP and TPP,finally discussed the impact factors of PDOC productivity.The results showed that the average contribution of PDOC to TPP in the Qinzhou bay could reach 15% during two seasons,which satisfies about 25% of carbon requirement by heterotopic bacteria in the bay. Multiple factors contribute to the seasonal(SW monsoon 13%middle bay 17%>inner bay 7%) in PER,the most significant of which are salinity and nitrogen to phosphorus ratios. PER is also related to phytoplankton community structure and nutrient limitation,the higher PER in the outer bay is attributed to the dual effect of picophytoplankton being the predominant species and a severe imbalance in the nitrogen to phosphorus ratio,both of which lead to increased phytoplankton PDOC release,while the lower PER in the inner bay was mainly due to the dominance of microphytoplankton and a nitrogen to phosphorus ratio close to the redfield ratio.There is still non-uniform conclusion on the relationship between PER and TPP, suggesting that this relationship needs to be evaluated not only in a horizontal-independent way,but also including seasonal and vertical dimensions.No-linear relationship between PDOC and BCD found in this study potentially indicates weak coupling between phytoplankton exudation and bacterial metabolism.In addition to phytoplankton exudes,the heterotrophic bacteria may satisfy with other sources of DOC to achieve their carbon requirement.We here speculate our findings could be applied to the correction of phytoplankton carbon sequestration in nearshore waters.We here speculate our findings could be applied to the correction of phytoplankton carbon sequestration in nearshore waters.